Pomegranate and Its Components, Punicalagin and Ellagic Acid, Promote Antidepressant, Antioxidant, and Free Radical-Scavenging Activity in Ovariectomized Rats - Cervantes-Anaya, Nancy; Azpilcueta-Morales, Gabriel; Estrada-Camarena, Erika; Ramírez Ortega, Daniela; Pérez de la Cruz, Veronica; González-Trujano, Maria Eva; López-Rubalcava, C. (Frontiers in Behavioral Neuroscience, 2022)
Previous reports described the antidepressant-like action of the aqueous extract of pomegranate (Punica granatum: AEPG). Thus we evaluated the effect of AEPG and the main compounds found in the extract, punicalagin (PNCG) and ellagic acid (EA), on forced swimming test and the redox environment (reactive oxygen species [ROS] production, lipoperoxidation [LPX], and cellular function) in the brain of rats treated with 3 weeks post ovariectomy exposed ex vivo to pro-oxidants. Also, we selected PNCG and EA to study their antidepressant-like effects (0.001, 0.01, 0.1, 1.0, and 10 mg/kg) in the forced swimming test and their scavenging capacities in chemical combinatorial assays (expressed as IC50 values). We observed a 2-fold increase in the formation of ROS and LPX in the brain after exposure to FeSO4. However, these effects were significantly attenuated when rats were treated with AEPG, PNCG, and EA (1 mg/kg and 0.010 mg/kg for 14 days). AEPG and EA significantly increased the cellular function values of brains that had been affected by the effect of FeSO4 and with ONOO–. PNCG and EA significantly reduced immobility behavior at the lower doses used in this study. The capacity of scavenging compounds to eliminate radicals was for hydroxyl radical (⋅OH), superoxide anion (O2⋅⁣–), and peroxynitrite (ONOO–) as follows: AEPG > punicalagin > ellagic acid. In conclusion, the AEPG and their active compounds PNCG and EA promote antidepressant-like actions and antioxidant activity as they attenuate oxidative damage and prevent cellular dysfunction in ovariectomized rat brains.